Analisis Sifat Mirip Obat, Prediksi ADMET, dan Penambatan Molekular Isatinil-2-Aminobenzoilhidrazon dan kompleks logam transisi Co(II), Ni(II), Cu(II), Zn(II) Terhadap BCL2-XL - Yesaya Reformyada Nusantoro; Arif Fadlan (Akta Kimia Indonesia, 2020)
This article reports an drug-likeness analysis, ADMET profile, and molecular docking of isatinyl-2-aminobenzoylhydrazone (ISABH) and its transition metals Co(II), Ni(II), Cu(II), and Zn(II) complexes. SwissADME analysis for drug-likeness indicated that ISABH and Ni-ISABH met all parameters of the Lipinski rule. These compounds also showed good pharmacological criteria by admetSAR for their ADMET prediction. The molecular docking of all compounds against the main regulatory protein for apoptosis BCL-2 (PDB code: 2W3L) revealed that they well-interacted with the protein expressed by binding affinity of -6.1, -8.3; -8.3; -7.5; and -8.5 kcal/mol for ISABH, Cu-ISABH, Co-ISABH, Ni-ISABH, and Zn-ISABH, respectively.